EDUKASI DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI INTERPERSONAL ANTARA SISWA TERHADAP GURU Di MI Al-HIDAYAH SEGARJAYA - Iftitah Sangadah; Winda Primasari; Nurlaila Maysaroh (Universitas Islam 45 Bekasi, 2022)
Many problems experienced by students in communicating. This is because students have different communication skills. Many problems experienced by students in communicating. This is because students have different communication skills. In this study, the research used educational methods to improve interpersonal communication in grade 1 to grade 3 students at MI Al Hidayah Segar Jaya Dusun Kali Asin 1, Batu Jaya sub-district. This education aims to provide knowledge about the importance of good and polite communication with friends and older people. With this education there are also changes in students at Mi Al-Hidayah, many students have applied the material provided.